Investigating E-Servicescape Influence to Customer Response In Digital Islamic Banking - Andriani, Prima; Setyorini, Noni; Shibghatalloh, Ahmad Hafiyyan (International Journal of Islamic Economics and Finance (IJIEF), 2021)
The mobile banking application is developed using the e-servicescape concept to create positive response in customers as application users. The objective of study is investigating the relationship between e-servicescape, trust, virtual word of mouth customer in Islamic banking. This study is quantitative approach that used Structural Equation Modelling (SEM). We collected data using an online questionnaire adapted from previous research, then distributed to all Islamic banking customers in Indonesia. The sampling technique used purposive random sampling involving 158 respondents with criteria such as Islamic bank customers in Indonesia who use mobile application services. The results of the study that all hypotheses are accepted. All dimensions of e-servicescape has a positive and significat effect on e-servicescape, e-servicescape has a positive and significat effect on trust, and trust has a positive and significant effect on customer virtual word-of-mouth. This research provides theoretical and practical contributions which will also be discussed further in this paper.